Analisis Penerapan Jadwal Retensi Arsip Dalam Pemusnahan Arsip Inaktif di Badan Keuangan dan Aset Daerah Kabupaten Malang - Salma Sana; Halid Hasan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Records Retention Schedule (RRS) is essential for managing the records lifecycle and preventing the accumulation of inactive files. However, its optimal implementation remains a challenge for many government agencies. This qualitative descriptive study aims to evaluate the implementation of the RRS in disposing of inactive records at the Regional Financial and Asset Management Agency (BKAD) of Malang Regency. Data were collected through observations, in-depth interviews, and documentation, then analysed using the Miles and Huberman interactive model. The findings reveal that RRS implementation at BKAD is highly suboptimal. Key obstacles include a centralized RRS that fails to accommodate the agency's specific financial record types, a shortage of skilled archival human resources, and the reluctance of record-creating units to dispose of files due to potential legal liabilities. Consequently, a massive accumulation of inactive records including 643 boxes of SP2D documents (2012–2016) and 96 linear meters of unstructured files (2008–2018) clutters the record centre floor. In conclusion, actual record disposal has been limited merely to duplicates rather than original records. Future research should observe post-improvement disposal processes and explore other local government agencies to develop a more adaptive RRS implementation model.